CD4+, CD8+ and FOXP3+ lymphocytes infiltrating oral leukoplakia: an immunohistochemical analysis - Castro, Tamara Fernandes de [UNESP] (2020)
Objective: To evaluate the infiltration of CD4+, CD8+ and FOXP3+ lymphocytes and their correlation with sociodemographic, clinicopathological and lifestyle characteristics of patients with oral leukoplakia. Patients and methods: Eighty patients diagnosed with oral leukoplakia were included in the study. Retrospective analyses were performed in order to verify the sociodemographic, clinicopathologic and lifestyle characteristics. The lymphocytic infiltrate characterization was performed by immunohistochemistry with antibodies against CD4+, CD8+, and FOXP3+ markers. Results: Of 80 patients included in the study, 60% were men, and their age ranged from 25 to 82 years, with a mean of 58.6. Thirty-eight patients (47.5%) were elderly, Thirty-two (40%) middle-aged, and only ten (10%) young adults. Sixty-one of the patients were smokers (76.2%) and forty-six were alcoholics (57.5%). Twenty-seven (35.5%) of the lesions presented some degree of dysplasia. The degree of epithelial dysplasia was correlated with the intensity of alcohol consumption (p=0.008). A positive correlation was found between CD4+ and CD8+ lymphocytes (p=0.005). Conclusion: The lymphocytic infiltrate of oral leukoplakia was not correlated with any clinicopathologic characteristic. However, the degree of epithelial dysplasia was correlated with the lifestyle of the patients.